Iron balance and iron supplementation for the female athlete: A practical approach. Issue 2 (7th February 2018) - Pedlar, Charles R; Brugnara, Carlo; Bruinvels, Georgie; Burden, Richard
ABSTRACT: Maintaining a positive iron balance is essential for female athletes to avoid the effects of iron deficiency and anaemia and to maintain or improve performance. A major function of iron is in the production of the oxygen and carbon dioxide carrying molecule, haemoglobin, via erythropoiesis. Iron balance is under the control of a number of factors including the peptide hormone hepcidin, dietary iron intake and absorption, environmental stressors (e.g. altitude), exercise, menstrual blood loss and genetics. Menstruating females, particularly those with heavy menstrual bleeding are at an elevated risk of iron deficiency. Haemoglobin concentration [Hb] and serum ferritin (sFer) are traditionally used to identify iron deficiency, however, in isolation these may have limited value in athletes due to: (1) the effects of fluctuations in plasma volume in response to training or the environment on [Hb], (2) the influence of inflammation on sFer and (3) the absence of sport, gender and individually specific normative data. A more detailed and longitudinal examination of haematology, menstrual cycle pattern, biochemistry, exercise physiology, environmental factors and training load can offer a superior characterisation of iron status and help to direct appropriate interventions that will avoid iron deficiency or iron overload. Supplementation is often required in iron deficiency; however, nutritional strategies to increase iron intake, rest and descent from altitude can also be effective and will help to prevent future iron deficient episodes. In severe cases or where there is a time-critical need, such as major championships, iron injections may be appropriate.